Upaya Meningkatkan Motivasi Belajar Siswa melalui Strategi Pembelajaran Resource Based Learning (RBL) dalam Pembelajaran IPA Kelas V di SDN 08 Tabek panjang - Raudhatul Indah; Laila Husni; Ratna Leni; Sukri Sikum (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The background of this study is low student motivation in the process of learning Islamic Education and Civic Education. This can be seen during learning activities, where only 8-9 students are active, even though the total number of students in grade V is 29. The rest of the students appear to be less enthusiastic in learning activities due to various factors, namely: students tend to get bored in class, and students lack mastery of the material. This learning model will help students think about the material independently and creatively. This research is a classroom action research (CAR). The research subjects are 29 fifth-grade students at SDN 08 Tabek panjang. The results of this study indicate that the Resource Based Learning (RBL) strategy that has been implemented can increase students' learning motivation in Natural Sciences (IPA) learning. This can be seen from the overall score of student learning motivation in cycle I of 58.02%, which is in the moderate category. Then, in cycle II, it increased again to 67.30% in the high category. So, it can be said that the actions taken were in line with expectations.